Toward a theology of migration: social justice and religious experience - Cruz, Gemma Tulud (Palgrave Macmillan's Content and context in theological ethics, 2014)
Foreword / by Robert Schreiter -- Introduction: Migration as a locus for theological reflection -- Migration and social justice. Living on the edge: migration, globalization, and the unskilled worker ; Old challenges, new contexts, and strategies: the experience of migrant women ; Citizen-disciples: an ethical roadmap for migration reform -- Migration and religious experience. Journeying (together) in faith: migration, religion, and mission ; Toward an intercultural church: migration and inculturation ; A pilgrim people: migration and spirituality -- Conclusion: One bread, one body, one people